Activation of «COVID» Words in the Kazakh Language: Statistical Analysis - Agabekova, Zh.; Amirbekova, A.; Kalybekova, K.; Ospanova, D.; Abylayeva, B.; Khassenov, B. (Forum for Linguistic Studies, 2024)
Some words in the Kazakh language became more actively used during the pandemic. This article describes which words were most often used in the Kazakh language during the COVID-19 pandemic. The research materials were taken from Google Trends and the National Corpus of the Kazakh language. The analysis showed that in the Kazakh language words like koronavırýs-coronavirus (noun); covid (noun); COVID-19 (noun); pandemıa-pandemic (noun); ózin-ózi oqshaýlaýself- isolation (pronoun+gesture name); lokdaýn-lokdaun (noun); áleýmettik qashyqtyq-social distance (adjective+noun); qashyqtyqtan oqytý-distance learning (noun+gesture name) were frequently used. The article has developed a visualization of the frequency of use of words with statistical diagrams. As a result of the study, we came to the conclusion that new words appeared in the Kazakh language that were actively used during the pandemic, it was also noticed in March 2020 that the words coronavirus, covid, COVID-19, pandemic were quite popular in the Kazakh language.
Keywords: Pandemic; COVID-19; Kazakh language